1998
DOI: 10.1093/toxsci/44.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Sublethal Exposure to the Protein Phosphatase Inhibitor Microcystin-LR Results in Multiple Dose-Dependent Hepatotoxic Effects

Abstract: The purpose of this study was to relate dose-dependent hepatotoxicity stemming from prolonged exposure to sublethal concentrations of the cyclic heptapeptide microcystin-LR (Mcyst) to hepatic Mcyst concentrations and protein phosphatase activity. Mcyst is a potent inhibitor of protein phosphatase types 1 and 2A (PP1 and PP2A). Twenty male Sprague-Dawley rats were infused continuously with 0, 3, 6, or 9 micrograms Mcyst/day for 28 days using intraperitoneal mini-osmotic pumps containing highly purified toxin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 0 publications
6
34
1
Order By: Relevance
“…In agreement with previous reports (Solter et al, 1998;Ito et al, 2000;Sedan et al, 2013) we found higher levels of MC-LR in liver of mice treated with the highest dose.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous reports (Solter et al, 1998;Ito et al, 2000;Sedan et al, 2013) we found higher levels of MC-LR in liver of mice treated with the highest dose.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our results indicate that prolonged and intermittent oral exposure at doses as low as 50 mg MC-LR/kg are capable of generating liver injury even when peripheral liver damage biomarkers remain unaltered. An important implication of these results from the clinical point of view, is that the measurement of plasma ALT, AST, and ALP is not the best choice of technique for detecting MC-LR exposure in a low-dose oral exposure scenario (Solter et al, 1998;Andrinolo et al, 2008). The experimental evidence supports the hypothesis that it is necessary to determine a range of parameters in addition to MC-LR plasma/urine quantification in order to more accurately evaluate microcystin exposure (Sedan et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations